Disclosures about algorithmic decision making in the corporate reports of Western European companies - Bonsón, Enrique; Bednárová, Michaela; Perea-Khalifi, David (Elsevier, 2023)
Over the last decade, the use of different artificial intelligence (AI) tools has increased. To shed some light on the emerging trend of AI disclosure, the aim of this paper is to analyse the current practices of major Western European companies regarding the automated decision-making (ADM) disclosure in their annual or sustainability reports. This paper proposes a methodology based on bigrams that enables the automatic extraction of the information on ADM that companies disclose. The sample consisted of 962 annual/sustainability reports, published in 2018 and 2019, of 337 companies listed on 13 Western European countries’ stock markets. Our findings show that ADM disclosure is still at an early stage and that the first adopters are mostly companies operating in the financial sector.
Keywords: Sistemas de soporte a la decisión; ADM; Artificial Intelligence; Content analysis; Corporate reporting; European companies